Enhancing AI-Powered PowerPoint Skills: Training Impact on Vocational Teachers in Surakarta - Subarno, Anton; Dyah Sulistyaningrum Indrawati, Cicilia; Ninghardjanti, Patni; Winarno, Winarno; Choerul Umam, Muhammad (Universitas Ahmad Dahlan, 2025)
Background: The integration of AI-powered PowerPoint in education offers promising opportunities for enhancing teaching effectiveness, yet many vocational teachers face challenges in implementing this technology due to limited training and technical support. Contribution: This study contributes to the educational community by providing a practical framework for integrating AI-powered tools in vocational education, thereby enhancing teachers' technical skills and supporting sustainable technological adoption. Method: Using a quasi-experimental design with a one-group pretest-posttest approach, twenty office administration teachers participated in an 8-hour training program. Data were collected through validated instruments measuring three indicators: training reaction, training facilities and materials, and expected behavioral changes. Results: Paired-sample t-tests revealed highly significant improvements in expected behavioral changes (t (19) = -4.501, p < 0.001) and training facilities perception (t (19) = -2.594, p = 0.018), although training reaction showed no significant change (t (19) = -1.628, p = 0.120). Conclusion: These findings suggest that intensive, well-structured training programs can effectively promote AI-powered PowerPoint adoption in vocational education, particularly in developing technical skills and implementation intentions. Educational institutions should consider implementing similar training programs while maintaining long-term support structures to reinforce learning and facilitate sustained technological integration.